2004
DOI: 10.2337/diacare.27.2.478
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of Blood Glucose Monitoring System Using the Internet

Abstract: OBJECTIVE -The Internet is used worldwide as a communication tool. To improve the quality of diabetes control, we investigated the effectiveness of an Internet-based blood glucose monitoring system (IBGMS) on controlling the changes in HbA 1c levels.RESEARCH DESIGN AND METHODS -We conducted a randomized clinical trial involving 110 patients who visited the outpatient clinic at the Kangnam St. Mary's Hospital for 3 months. The study subjects were treated with IBGMS for 12 weeks, and the control group received t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
163
0
5

Year Published

2005
2005
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 181 publications
(172 citation statements)
references
References 21 publications
4
163
0
5
Order By: Relevance
“…While government-led telehealth initiatives tend to focus on video conferencing, a number of small studies and pilot projects delivering health services via the Internet have been reported in patients with breast cancer (21,22), asthma (23), chronic obstructive pulmonary disease (24,25), diabetes (26)(27)(28)(29)(30)(31)(32), lung transplantation (33), overweight (34)(35)(36)(37)(38)(39)(40), smokers (41), chronic heart failure (25,(42)(43)(44) and CVD (45)(46)(47)(48). These studies demonstrated that patients were willing to enter self-measured data online and communicate with health care providers via e-mail and/or chat/video conferencing.…”
Section: Discussionmentioning
confidence: 99%
“…While government-led telehealth initiatives tend to focus on video conferencing, a number of small studies and pilot projects delivering health services via the Internet have been reported in patients with breast cancer (21,22), asthma (23), chronic obstructive pulmonary disease (24,25), diabetes (26)(27)(28)(29)(30)(31)(32), lung transplantation (33), overweight (34)(35)(36)(37)(38)(39)(40), smokers (41), chronic heart failure (25,(42)(43)(44) and CVD (45)(46)(47)(48). These studies demonstrated that patients were willing to enter self-measured data online and communicate with health care providers via e-mail and/or chat/video conferencing.…”
Section: Discussionmentioning
confidence: 99%
“…İyi bir metabolik kontrol sadece kendi kendine düzenli bir kan şekeri ve glikolize hemoglobin (HbA1c) takibi ile yeterli olmayıp, bireyin diyabete uygun tıbbi beslenme tedavisi ve yapacağı yaşam tarzı değişiklikleri konusundaki bilinçlenmesiyle de ilişkilidir (10,11). Diyabetin etkili yönetim ve kontrolü sağlık personelinin hasta ve ailesinin duyarlılığını arttırması ve hastalığa ilişkin tutumlarını olumlu yönde değiştirmesi ile sağlanabi-lir (10,12,13,14).…”
unclassified
“…For this purpose, different strategies using electronic technologies or educational programs have been proposed to improve the quality and efficiency of care for people with diabetes (8 -15). In our previous study (16), we introduced a new bidirectional communication tool for diabetes management referred to as the Internet-based glucose monitoring system (IBGMS) and demonstrated its short-term effects over 3 months. The IBGMS comprises an electronically organized circuit for diabetes management that includes both online and offline systems.…”
mentioning
confidence: 99%